Study of adaptive frequency notched radar waveform - Guo, Yitong (2014)
Adaptive frequency notched radar waveform is examined in this report. The signal sent out by radar will encounter interference and noise when transmitting through the air. Then, when the interfered signals are transmitting back, the matched filter outcome will not be good because of the interference. If we know which range of frequency will be interfered, we could remove that frequency from the whole band before sending out the signal. Thus, the matched filter outcome will be improved a lot. The two different kinds of frequency notched radar waveform are examined in this report. Ultra-low sidelobe waveform is another way to improve the matched filter outcome and lower down the sidelobe level. By changing the time versus frequency waveform from the simple linearity, we expect the performance of matched filter output will be improved. To achieve this, we added two tails with different slope to the original linear graph. Besides, LFM windowing can also reduce the sidelobe level. It simply adds a window function between the matched filter impulse response and received signal. PSO (Particle Swarm Optimization), as the stochastic evolutionary computation optimization technique is also introduced in this report. Deriving from the ultra-low sidelobe waveform, we aim to make it a generalization and find an optimization. By using the PSO method, we expect to come out a best design of time versus frequency waveform in order to achieve a low sidelobe. Also, we use PSO to optimize the notched frequency radar waveform. In this report, the software part of adaptive notched radar waveform is studied. By using the software Matlab, we simulate the performance and matched filter output of radar waveform.